Investigation of ultrasonic non-destructive testing capabilities on honeycomb sandwiched structures - Ang, Javier Zetian (Nanyang Technological University, 2021)
Experimental research had been conducted to investigate the detection of adhesive defects found within the honeycomb sandwiched structure using A-Scan of Ultrasonic Pulse Echo Inspection and Through Transmission Inspection, specifically if the probe was on the opposite side of the defect. Experiments were first conducted to research the effects of thickness of honeycomb core using Ultrasonic A-Scan of Steel Feeler Gauges of varying thickness. With increasing thickness of the Feeler Gauges, it was discovered that the signal to noise ratio decreases, which was attributed to the signal zig-zagging effect. Ultrasonic Inspection of Honeycomb Structures were also investigated. It was found that in the Pulse Echo inspection of honeycomb structures with face plates made of Steel or Aluminium, the defect is detectable if the probe was on the faceplate interface where the adhesive defect is present. The measurement of the defect size using similar methodologies to 6dB method was also possible with high accuracy. However, when the probe was placed on the opposite side of the defect of honeycomb structure made from Steel/Aluminum face plates, the detection of the defect was no longer possible. The inspection of honeycomb structures made from Acrylic face plates yielded different results where the Pulse Echo Inspection was able to detect the adhesive defect regardless if the probe was on the same side or opposite side of the defect. This was deduced to be due to the small differences in acoustic impedance between the acrylic plates and the adhesive, allowing transmission while the large differences in acoustic impedance between the steel/aluminum plates and the adhesive prevented transmission and caused reflection. Through Transmission methodologies were also employed to replicate the industrial standards of detecting such a defect.